Bioenergy Recovery from Anaerobic Co-Digestion of Sugarcane Vinasse and Dairy Cattle Wastewater in Two Up-Flow Anaerobic Sludge Blanket Reactors in Series - de Santi Caraça, Michel [UNESP]; de Oliveira, Roberto Alves [UNESP]; Duda, Rose Maria [UNESP] (Springer Nature, 2023)
Anaerobic co-digestion (AcoD) may be an interesting option to improve the operating conditions of anaerobic reactors used in vinasse treatment and provide an alternative for dairy cattle wastewater (DCW) management in regions near to ethanol industries. This work aimed to evaluate the effect of AcoD of sugarcane vinasse with DCW (84.8% and 15.2% of COD, respectively) in two up-flow anaerobic sludge blanket reactors (UASB—R1 and R2) in series. The improvements in the nutritional conditions of the vinasse because of the co-digestion with the DCW, combined with effluent recirculation, provided average removals of total COD of 77% for the overall system (R1 + R2) and volumetric methane production of 0.451 m3 CH4 (m3 d)−1 for R1. From the theoretical potential of electrical power production, we verified the possibility of producing 10.65 kWh d−1 per m3 of vinasse in the UASB reactors. That is 39% of the electrical energy needed to process one ton of sugarcane. Therefore, anaerobic co-digestion is an attractive alternative for energy use and reducing environmental problems of vinasse and DCW.
Keywords: Anaerobic reactors; Biogas; Methane; UASB reactor